2011
DOI: 10.1186/gb-2011-12-12-r126
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and their isomiRs function cooperatively to target common biological pathways

Abstract: BackgroundVariants of microRNAs (miRNAs), called isomiRs, are commonly reported in deep-sequencing studies; however, the functional significance of these variants remains controversial. Observational studies show that isomiR patterns are non-random, hinting that these molecules could be regulated and therefore functional, although no conclusive biological role has been demonstrated for these molecules.ResultsTo assess the biological relevance of isomiRs, we have performed ultra-deep miRNA-seq on ten adult huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
335
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(354 citation statements)
references
References 76 publications
15
335
1
3
Order By: Relevance
“…Due to imprecise cleavage of miRNAs from precursor miRNA hairpins [2325], one miRNA locus can produce multiple isoforms, termed isomiRs, which can differ by one or two nts at the 5ʹ start position. Consequently, the canonical miRNA “seed” sequence is altered, potentially conferring recognition of different mRNA targets [2426].…”
Section: Resultsmentioning
confidence: 99%
“…Due to imprecise cleavage of miRNAs from precursor miRNA hairpins [2325], one miRNA locus can produce multiple isoforms, termed isomiRs, which can differ by one or two nts at the 5ʹ start position. Consequently, the canonical miRNA “seed” sequence is altered, potentially conferring recognition of different mRNA targets [2426].…”
Section: Resultsmentioning
confidence: 99%
“…This fact is of profound importance for miRNA's function, because the addition or deletion of nucleotides at the isomiR 5 0 end results in a change in the seed region and, consequently, leads to the regulation of a distinct set of target genes compared to the isomiR's canonical counterpart. As functional partners of their reference canonical molecules, isomiRs are tissue specific; therefore, the proper interpretation of microRNA-regulated networks requires comprehensive information on the miRNome for each particular tissue type (15,16,17).…”
Section: Microrna Function and Biogenesismentioning
confidence: 99%
“…It is implausible that the whole phenomenon is simply a manifestation of noise in the system, although this may well be the case for individual examples. Expression of miRNA variants has been hypothesized to facilitate robust repression of a core set of mRNAs they target collectively, whereas potential individual off-targeting effects of each variant are ''diluted out'' by its relatively lower abundance (32). Another possibility is that miRNA sequence variants may be differentially localized and regulated or otherwise may associate with diverse effector proteins to create distinct outcomes (e.g., translational repression vs. mRNA decay).…”
Section: Mirna Processing Variantsmentioning
confidence: 99%
“…start sites are generated by differential Drosha or Dicer processing and have shifted seed sequences relative to the canonical miRNA. 5 0 isomiRs may thus have differential targeting properties and experiments indeed showed that they bind both common and unique targets (32). Additionally, there is experimental evidence that 5 0 isomiRs of the cardiac miR-133a can have selective mRNA repression properties (34).…”
Section: Mirna Processing Variantsmentioning
confidence: 99%
See 1 more Smart Citation